Cardiac Infiltration as the First Manifestation of Acute Lymphoblastic Leukemia: A Systematic Review - Luo, Zhi; Cheng, Jun; Wang, Yanggan (Frontiers in Oncology, 2022)
Cardiac symptoms or signs as the first manifestations in acute lymphoblastic leukemia patients are sporadically reported which lead to misdiagnosis or delayed diagnosis due to lack of clinical experience and improper diagnosis procedures. Here, we documented the clinical features, procedures of diagnosis, treatments and outcomes from the so-far reported 30 lymphoblastic leukemia cases that initially presented as cardiac problems and provided management recommendations based on the experiences and lessons learned from these patients to help physicians avoid misdiagnosis and improper treatment.